The Hope of Refuge : A Novel - Woodsmall, Cindy (Colorado Springs, Colo. : Waterbrook Press, 2009)
Struggling against poverty and a relentless stalker, Cara Moore, a widowed mother, is led out of New York City toward an Amish community in Dry Lake, Pennsylvania, where she quickly discovers long-held secrets about her family.
Keywords: Amish -- Fiction; Fiction